MOSQUE CONSTRUCTION FEATURES OF THE KAZAKH PEOPLE (THE MIDDLE XIX – EARLY XX CENTURIES) - K.K. Rakhbayev,; R.A. Beknazarov,; I.V. Stasevich, (Academic Journal of Physical and Chemical Sciences, 2019)
According to official historiography, a stone mosque in Petropavl is considered to be the oldest mosque in Kazakhstan and the first mosque built by the Kazakhs was built in 1835 organized by Zhangir Khan in the Bukey Horde, also known as the Inner Horde. The first mosques built by Aral - the Caspian Region Kazakhs started in the late XVIII - early XIX centuries represented by the Mosque Aday Beket-Ata built by Myrzagululy on the bank of the Zhem River. The next stage of the mosque history (XIX century) is related to the names of the historical figures, prophets Tabyn Doszhan Ishan and Tama Nurpeke. Doszhan Ishan was among those first who built the mosque near the Kaynar Spring that is in the Tasastau tract, on the ridge of Dongyztau. The mosque of Doszhan Ishan Kashakuly in the Tasastau-Kaynar was built in the 50s of XIX century.